2011
DOI: 10.1002/art.30354
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of systemic and local myeloid cell subpopulations by bone marrow cell–derived granulocyte–macrophage colony‐stimulating factor in experimental inflammatory arthritis

Abstract: Objective. Even though there are clinical trials assessing granulocyte-macrophage colony-stimulating factor (GM-CSF) blockade in rheumatoid arthritis (RA), questions remain as to how GM-CSF acts as a proinflammatory cytokine. The aims of this study on the regulation of arthritis progression by GM-CSF were to determine the source of the GM-CSF, whether there are systemic effects, the changes in synovial tissue leukocyte populations, and the arthritis model dependence on GM-CSF.Methods. Bone marrow chimeras were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
55
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 50 publications
7
55
0
Order By: Relevance
“…[30][31][32] In CIA, macrophages play a preeminent role in driving disease. Targeting molecules that promote macrophage proliferation, accumulation or activation (eg, CSF-1, granulocytemacrophage colony-stimulating factor, TNF-a, IL-1b, and IL-6) [33][34][35][36][37][38][39][40] suppresses CIA in mice. As has been reported using antibodymediated macrophage depletion, 41 we found that macrophage depletion by systemic clodronate administration resulted in amelioration of CIA to an extent analogous to what was observed with uPAdeficient mice (data not shown).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[30][31][32] In CIA, macrophages play a preeminent role in driving disease. Targeting molecules that promote macrophage proliferation, accumulation or activation (eg, CSF-1, granulocytemacrophage colony-stimulating factor, TNF-a, IL-1b, and IL-6) [33][34][35][36][37][38][39][40] suppresses CIA in mice. As has been reported using antibodymediated macrophage depletion, 41 we found that macrophage depletion by systemic clodronate administration resulted in amelioration of CIA to an extent analogous to what was observed with uPAdeficient mice (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Each of these cell types has been shown to express both uPA and uPAR, 19,[44][45][46][47] and each has been linked to arthritis pathogenesis in both RA and CIA. 20,33,[48][49][50][51] Whether uPA/uPAR-dependent mechanisms of arthritis pathogenesis occur through multiple hematopoietic cell types and whether these mechanisms require uPA production by one cell type and uPAR expression by another remain to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, TNF-a induces MDSC proliferation in s.c. tumor models (48) and chronic inflammation models (49). The level of GM-CSF is elevated in experimental inflammatory arthritis (50), and GM-CSF is critical for the proliferation of MDSCs in cancer (51). MDSCs may accumulate in response to increased level of TNF-a and/or GM-CSF in CIA.…”
Section: Discussionmentioning
confidence: 99%
“…At termination, the knee joints were removed, fixed, decalcified and paraffin embedded 9 14 20. Frontal sections (5 μm) were stained with H&E. For antigen-induced arthritis (AIA), infiltration of cells, cartilage damage and bone erosions were scored separately from 0 (normal) to 3 (severe) 20.…”
Section: Methodsmentioning
confidence: 99%